Tenaga Kesehatan, Dukungan Suami, Motivasi, Konsep Diri dan Kesehatan Fisik terhadap Mekanisme Koping Wanita Infertil : Health Workers, Husband's Support, Motivation, Self-Concept and Physical Health on Infertile Women's Coping Mechanisms - Hendarwan, Harimat; Saputri, Dira (MPI Press, 2022)
Introduction: A woman who can not give birth to a child, then her social status is considered inferior if there are no adjustments and good handling, which can put pressure resulting in their impaired psychology and even physical fitness. The right coping mechanism is necessary to overcome a problem caused by infertility Objectives: The purpose of this research is to know the influence of the direct and indirect role of health workers, support husbands, motivation, self-concept, and the welfare of the physical coping in women with infertility in hospital mother and child WEMPE Singkawang City in 2018. Method: This type of research is quantitative using the descriptive-analytic method with a cross-sectional approach. The population in this study were all infertile women who were examined from May to December at the WEMPE Mother and Child Hospital Singkawang City with a total of 114 people. The number of samples was taken following the number of samples in the PLS (Partial Least Squares) guidelines a multiple of the number of indicators to be studied. Data analysis using Partial Least Square (PLS) approach using smart PLS software. Result: The research results show that the coping mechanism in women with infertility is influenced by the role of a trained health professional (12,92%), support of husbands (13,14%), motivation (20,48%), self-concept (19.75%) and the welfare of physical (29,07%). The direct effect of women’s coping mechanism for infertility is 95.4 % and as much as 1,86 % is an indirect effect. Relevance predictive value ( Q Square ) is 99,9 % while 0,01 % is described by other variables that were not investigated. Conclusion: Thus it can be concluded that the health of physical mechanisms for fear of a massive coping. With the condition of good health, women infertile will find it easy to cope with overcoming the problem generated by infertility.